Bacterial cellulose filled epoxy resin-based green composites: fabrication and characterization. Issue 7 (2nd July 2020) - Bach, Quang-Vu; Manh Vu, Cuong
ABSTRACT: The bacterial cellulose (BC) was extracted from nata-de-coco and used as green reinforcement material for epoxy resin. In order to enhance the chemical affinity of BC and epoxy resin the surface of BC was decorated with silane coupling agent. Many techniques were also used to assist the dispersion of BC in epoxy resin such as: mechanical stirrer, grinding and ultrasonication. The green composite of BC in epoxy resin was obtained from hot curing processing using methylhexahydrophthalic anhydride as hardener. The characteristics of green composite such as mechanical properties, thermal stability, fracture toughness and fracture surface were studied in detail. The silane coupling agent with epoxide group can be participated in curing reaction with epoxy resin and helped to enhance the mechanical properties and fracture toughness of epoxy resin. Micro crack, stopping the crack, and changing the crack pathway were considered as main mechanisms of improvement of fracture energy.